Le retour de Bouvard et Pécuchet - Patrizia Oppici (Flaubert: Revue Critique et Génétique)
Bouvard et Pécuchet, the work that Flaubert devoted entirely to stupidity, is often taken up and commented from a philosophical point of view, rather than taking into consideration the psychological plausibility of the two protagonists. However, from Proust to a few contemporary rewrites, this literary couple has inspired authors who have adapted the adventures of the two fellows to the customs of different times, from end-of-the-century Paris to 1980s France, by reactivating the perverse circuit that leads them from failure to failure.